(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract Urban sustainability is a growing concern for economies experiencing rapid urbanization. Bengaluru’s evolution as a global city exemplifies the complex interplay between economic growth and sustainable urban practices. This paper examines sustainability initiatives in Bengaluru, their economic implications, and challenges such as infrastructure deficits and environmental degradation. Recommendations focus on integrating sustainable practices with economic planning to ensure balanced development.